United Construction Contract And Responsibilities In The People's Research And Assistance Offices - Yalid Yalid; Irawan Harahap; Riantika Pratiwi (International Journal Labs, 2024)
The purpose of this research is to explain the construction unit work contract and the responsibility for the risk of building failure that can be applied to one of the government procurement of goods and services at the Pekanbaru Search and Rescue Office. This research method is carried out through a stage in accordance with this type of research, namely empirical juridical. The result of this research found that the construction unit work contract and the responsibility for the risk of building failure at the Pekanbaru Search and Rescue Office should have been carried out by direct appointment. However, the procurement was instead carried out through a tender mechanism. The reason is that the Commitment Making Officer, Goods/Services Procurement Committee at the Pekanbaru Search and Rescue Office are not aware of the direct appointment rule. Liability for building failure if the construction unit work contract and responsibility for the risk of building failure at the Pekanbaru Search and Rescue Office are carried out without a direct appointment will be difficult to determine the responsibility. The construction service provider, whether it is the first construction work or construction consultancy, cannot be held liable for building failure if the building failure is caused by the fault of the follow-up work carried out by a different construction service provider. Conversely, it is also difficult for the construction service provider of the follow-on works to be held liable if the fault lies with the first construction works or construction consultancy